UPAYA DAN STRATEGI PEMENUHAN STANDAR NASIONAL PENDIDIKAN - Damanik, Jafriansen (Jurnal Dinamika Pendidikan, 2015)
Principally, all the education institutions are obliged to implement and improve the quality assurance in order to fulfil as well as to improve education national standard. For the assurance of the education quality control, it needs to do an evaluation, accreditation and certification. In reality, there are still many schools and other education institutions which do not make a great effort to fulfill the obligation. The purpose of this study is to find out the effort and strategy which are done by schools to fulfill national education standards. This research method applied an interview and documentation. The results of this research showed that some efforts that must be done by schools and other education institution consist of the standard of the content, process, graduate outcomes, education personnel, facilities and equipment, management, funding, and education assessment. Some strategies needed to implement by schools and other national education institution in order to fulfill the education national standard are: using all the ready potent, making plan and work program needed, encourage all the schools component in order to improve their work activities, appointing quality control, improving teaching and learning tools, strengthening the schools regulations procedure, expanding work team with business industry as well as stakeholders, school committee, the control official team, and government, facilitating teachers and education administrative staff to improve their competence, evaluating each of the program conducted and documenting all the school activities held.Keywords : national education standards, effort, strategy